2020
DOI: 10.1038/s41598-020-69433-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of an automated-machine learning development tool for predicting burn sepsis: proof of concept

Abstract: Sepsis is the primary cause of burn-related mortality and morbidity. Traditional indicators of sepsis exhibit poor performance when used in this unique population due to their underlying hypermetabolic and inflammatory response following burn injury. To address this challenge, we developed the Machine intelligence Learning optimizer (MiLo), an automated machine learning (ML) platform, to automatically produce ML models for predicting burn sepsis. We conducted a retrospective analysis of 211 adult patients (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 15 publications
(29 reference statements)
0
39
0
Order By: Relevance
“…The machine learning (ML) aspects of this study were carried out through the Machine Intelligence Learning Optimizer (MILO) automated ML platform (MILO ML, LLC, Sacramento, CA) which has been published in several recent papers 15 – 18 . Briefly, MILO includes an automated data processor, a data feature selector (ANOVA F select percentile feature selector and RF Feature Importances Selector) and feature set transformer (e.g., principal component analysis), followed by its custom supervised ML model builder using its custom hyperparameter search tools (i.e., its custom grid search along with its random search tools) to help find the optimal hyperparameter combinations within the variety of its embedded supervised algorithms/methods (i.e., deep neural network [DNN], logistic regression [LR], naïve Bayes [NB], k-nearest neighbor [ k- NN], support vector machine [SVM], random forest [RF], and XGBoost gradient boosting machine GBM]).…”
Section: Methodsmentioning
confidence: 99%
“…The machine learning (ML) aspects of this study were carried out through the Machine Intelligence Learning Optimizer (MILO) automated ML platform (MILO ML, LLC, Sacramento, CA) which has been published in several recent papers 15 – 18 . Briefly, MILO includes an automated data processor, a data feature selector (ANOVA F select percentile feature selector and RF Feature Importances Selector) and feature set transformer (e.g., principal component analysis), followed by its custom supervised ML model builder using its custom hyperparameter search tools (i.e., its custom grid search along with its random search tools) to help find the optimal hyperparameter combinations within the variety of its embedded supervised algorithms/methods (i.e., deep neural network [DNN], logistic regression [LR], naïve Bayes [NB], k-nearest neighbor [ k- NN], support vector machine [SVM], random forest [RF], and XGBoost gradient boosting machine GBM]).…”
Section: Methodsmentioning
confidence: 99%
“…Optimizer (MILO) platform (Regents of the University of California, Oakland) 14. This automated ML platform has been used for sepsis prediction previously in severely burned patients.…”
mentioning
confidence: 99%
“…In comparison, the auto-ML approach produced an enhanced k-nearest neighbor model which using only five features had a model accuracy of 90% and a ROC-AUC of 0.96. 11 This study not only displayed the improved performance of the auto-ML approach but also showed the need for much fewer features within the final optimized model, something that could be of great utility in clinical applications for critical pragmatic considerations. As noted, less dependency on the number of features within a model is very important from a practical standpoint since not all data is obtained at every time point within routine clinical practice.…”
Section: Auto-ml Proof Of Concept Studiesmentioning
confidence: 79%